Análisis del comportamiento de licuación por flujo de la arena del depósito cuaternario de Paipa (Boyacá) (2016)
Liquefaction is the process by which saturated land, without cohesion, changes from a solid material to one that behaves like a viscous material, due to the application of static or dynamic loads.  When the land enters into a state of liquefaction it does not withstand the applied load, producing slipping, flows, sinking or tilting of structures, among others.  The study of this phenomenon and the damage it causes, began after the earthquake in Niigata (Japan), in 1964.  Many experiments regarding this have been conducted, however, there are still many unknowns to be resolved regarding the behavior of granular land under the application of static loads.In order to carry out this experiment, we performed Consolidated Undrained triaxial tests, on sand from the Quaternary deposit in the city of Paipa, seeking to determine the parameters of liquefaction due to material flow, under the application of a monotonic load.  The material was characterized, defined as a silty sand, well graded, with fine grains content close to 30%.  The samples tested were constructed using the methods wet tamping and sedimentation in water, according to the grain-size composition of the material and with different relative density values.  Finally, the behavior of the material was evaluated, determining the lines of critical state and of transformation phase.  The sand studied showed the predominance of a delaying tendency, in its behavior, providing evidence of a low level of susceptibility to liquefaction.